Positron Emission Tomography in Coronary Heart Disease - José de Almeida; Sofia Martinho; Lino Gonçalves; Maria Ferreira (Applied Sciences, 2022)
With advances in scanner technology, postprocessing techniques, and the development of novel positron emission tomography (PET) tracers, the applications of PET for the study of coronary heart disease have been gaining momentum in the last few years. Depending on the tracer and acquisition protocol, cardiac PET can be used to evaluate the atherosclerotic lesion (plaque imaging) and to assess its potential consequences—ischemic versus nonischemic (perfusion imaging) and viable versus scarred (viability imaging) myocardium. The scope of this review is to summarize the role of PET in coronary heart disease.